Proposing My Reading Experience Questionnaire (MREQ) as an instrument to measure reading motivation and reading comprehension - Chong, Su Li; Dahlia Janan,; Sumathi Renganathan,; Lim, Jiai Wei; Suparman, (Penerbit Universiti Kebangsaan Malaysia, 2022)
The reading experience in the Malaysian context is often perceived and understood as being about reading in specific languages. Particularly, research in the field of English as a Second Language is replete with work on reading motivation. However, in this paper, it is argued that reading needs to be seen as going beyond language, setting reading as an experience rather than an ability. This paper therefore sets out to validate the My Reading Experience Questionnaire (MREQ) through a discussion of the questionnaire design as well as the statistical data validation based on the questionnaire items. From there, reading motivation levels of primary school children in Malaysia is analysed. 544 primary school children aged 8 and 11-yearsold completed the MREQ . Findings from the questionnaire were matched with the Malay language reading comprehension levels of these children. Both the validation and comparisons showed that the MREQ not only gauges reading motivation levels but also reveals the complexities that come with Malaysia’s multilingual literacy context in schools. This paper concludes by proposing for the MREQ to continue to be used especially with how its design is underpinned by sociocultural theories of language and literacy.